ESSAY: DIDACTIC ASPECTS OF ORGANIZATION OF EFFECTIVE INDIVIDUAL EDUCATIONAL WORK OF STUDENTS - Добротвор, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The problems of organization and control of effective individual work of students due to European requirements of fixation of laboriousness of learning activities were considered. On the example of one of the most common in practice of higher educational establishments kinds of individual work - writing an essay - didactic foundations of achievement of learning outcomes in a specific academic hour are represented